2005
DOI: 10.1143/jjap.44.3474
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Equalized Partial Response Path-Feedback Maximum Likelihood for 35.4 GB Blu-ray Disc ROM

Abstract: In this paper, we consider the acoustic phonon radiation by the plasma waves of quasi-two-dimensional inversion electron layers. The electron-phonon interaction is taken into account using the phenomenological deformation potential in the jellium model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…The adaptive equalized signal is inputted to the ITR block. To improve the qualities of the phase error, a fixed delay tree search (FDTS) detector 13) has been adopted for the assumed partial response (PR) class of the adaptively equalized signal. The FDTS detector has better bit-error rate (bER) performance characteristics for the PR-equalized signal than the threshold level detector.…”
Section: General Theory Of Mmse Itr Pll With Lcafmentioning
confidence: 99%
See 3 more Smart Citations
“…The adaptive equalized signal is inputted to the ITR block. To improve the qualities of the phase error, a fixed delay tree search (FDTS) detector 13) has been adopted for the assumed partial response (PR) class of the adaptively equalized signal. The FDTS detector has better bit-error rate (bER) performance characteristics for the PR-equalized signal than the threshold level detector.…”
Section: General Theory Of Mmse Itr Pll With Lcafmentioning
confidence: 99%
“…The FDTS also has a shorter decision delay than VD for minimizing loop delay. The phase error is calculated by the decision-directed timing error detection method 6,13,14) for the PR-equalized signal. The fractional sample second-order AVF 12) is placed before the interpolator of ITR PLL.…”
Section: General Theory Of Mmse Itr Pll With Lcafmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, several approaches to signal processing have also been examined in Blu-ray technologies. [2][3][4] Miyauchi et al 2) have demonstrated that a novel trellis decoding technique for the 17-parity preserve/prohibit (17PP) code is effective for increasing the recording density of the Blu-ray disc. Ohkubo et al proposed a new low-density parity-check (LDPC) coded partial response (PR) 17PP system.…”
mentioning
confidence: 99%